Pengembangan Website Promosi Produk UMKM Berbasis Online - Dodi Solihudin; Fathurrohman; Marfelio Muhamad Fajid; Mochamad Adhari Febrian (CV. Multi Kreasi Media, 2023)
Micro, Small, and Medium Enterprises (MSMEs) require effective promotion strategies to enhance the visibility and competitiveness of their products, especially in the digital era. This Community Partnership Program aims to develop product promotion websites for MSMEs based on WordPress. Activities include basic training on using the WordPress platform, designing and developing attractive and informative websites, simple search engine optimization (SEO) of content, and website management training for MSME representatives. It is expected that with this promotional website, MSMEs can expand their online market reach, enhance product brand image, and facilitate interaction with potential consumers, ultimately contributing to increased sales and business growth.